Characteristics and Etiologies of Chronic Scrotal Pain: A Common but Poorly Understood Condition. (2nd March 2017) - Aljumaily, Aosama; Al-Khazraji, Hind; Gordon, Allan; Lau, Susan; Jarvi, Keith A.
Abstract : Chronic scrotal pain (CSP) is a common and debilitating condition, but the underlying characteristics and etiology of CSP are poorly understood. The objective of this study is to identify the characteristic and etiologies of CSP. Men presenting for management of CSP completed a standardized questionnaire and underwent a complete physical examination. From Feb 2014 to Sep 2015, a total of 131 men (mean age 43) with CSP were studied. The CSP was of long duration (mean of 4.7 ± 5.95 years) and dramatically affected men's lives, with adverse effects on normal activities (71.%), ability to work (51.90%), and sexual functioning (61.8%). 50.4% felt depressed on most days, and 67.17% felt either unhappy or terrible with their present condition. Physical examination revealed that the epididymis was the most common tender area found in 70/131 men (53.43%), though a musculoskeletal source for the pain was found in 9.9%. Neuropathic changes were found in 30%. For close to half of the men (43.5%) we were unable to identify any potential cause for the CSP. This study characterizes the dramatic impact that CSP has on the lives of men, while providing an understanding of the common etiologies.